Management of venous ulcers in the Home Care Service: experience report (Research, Society and Development, 2022)
Introduction: Chronic Venous Insufficiency is considered a clinical condition usually manifested by the presence of edema, pain, dilated veins, hyperpigmentation and venous ulcers (VU), being triggered by reflux changes or by nerve obstruction of the lower limbs. The occurrence of VU can cause social difficulties for people who are affected, making adherence to timely treatment offered by a trained multidisciplinary team essential. Objective: To report the experience lived through the follow-up of a user registered in the Home Care Service in a city in the northeastern countryside. Methods: This is an experience report during the course of Supervised Practice in the postgraduate course in Public and Family Health of a private institution of higher education, with the follow-up of a user affected by VU registered in the Service of Home Care, in the city of Parelhas/RN, in December 2021. Results: The treatment of VU is an ongoing process that requires from nursing, in addition to practical skills, zeal for ethics, economy and social responsibility. Therefore, adherence to care is a challenge present at all times of treatment. In this context, the nurse has the role of acting as a mediator, enabling the patient to learn, making him develop his autonomy, making him independent in terms of his daily care. Final Considerations: With the experience from the practice of care, the dynamics, the need for a holistic view and the learning opportunities offered within the scope of the Unified Health System are reaffirmed.